Effect of periostin (OSF-2) on phagocytosis of Plasmodium-infected erythrocytes - Chin, Joo-Yie; Mohammed-Syafiei, Muhammed-Nur-Iman; Lim, Yi-Jun; Chong, Gordon Xue-Zhen; Suhaimi, Muhammad-Nasreen; Phong, Zhi-Ying; Ng, Yee Ling; Lau, Yee-Ling; Sam, I-Ching; Rénia, Laurent; Lee, Wenn-Chyau (Frontiers in Microbiology, 2025)
IntroductionPhagocytosis is a pivotal component of the human innate immune defense against malaria. This essential defense mechanism is often modulated by various host-derived soluble factors. We investigated the phagocytosis of Plasmodium falciparum- and P. knowlesi-infected erythrocytes (IRBC) by human monocytic THP-1 cells in the presence of periostin (OSF-2), a human secretory protein involved in inflammation and tissue repair. This focus was prompted by the fact that OSF-2 is a potent stimulator of Plasmodium IRBC rosette formation, a parasite-derived cytoadherence phenomenon known to impede phagocytosis.MethodsCulturable parasite isolates were recruited, and tested with the THP-1 cells and recombinant human OSF-2 protein. The role of OSF-2 in IRBC phagocytosis by the phagocytes was evaluated in the presence and absence of uninfected erythrocytes (URBC), and the receptor involved was investigated with antibody blocking assay.ResultsOSF-2 exerted a dual role. When rosetting was prevented via IRBC purification, OSF-2 increased IRBC phagocytosis. This stimulatory effect was also seen when THP-1 cells were primed with OSF-2 before IRBC exposure. This OSF-2-mediated phagocytosis was CD36-dependent and rapidly reversible upon OSF-2 removal. However, when rosetting was induced by the addition of URBC, the presence of OSF-2 reduced the rate of IRBC phagocytosis.DiscussionThese findings highlight the complex parasite-host interactions influencing the infection pathogenesis.